2020
DOI: 10.3389/fendo.2020.606744
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Application of AMH Measurement in Assisted Reproduction

Abstract: Anti-Müllerian hormone reflects the continuum of the functional ovarian reserve, and as such can predict ovarian response to gonadotropin stimulation and be used to individualize treatment pathways to improve efficacy and safety. However, consistent with other biomarkers and age-based prediction models it has limited ability to predict live birth and should not be used to refuse treatment, but rather to inform counselling and shared decision making. The use of absolute clinical thresholds to stratify patient p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 61 publications
(81 reference statements)
2
11
0
Order By: Relevance
“…In agreement with previous studies (4,(38)(39)(40)(41), the number of total oocytes, metaphase II oocytes, and >14 mm follicles were statistically different in groups in our study, verifying the positive predictive value of baseline AMH levels on the ovarian response to stimulation regimen. The total consumption of gonadotrophins progressively decreased from low to high baseline in the AMH group, which is consistent with previous data indicating that baseline AMH levels positively predict ovarian responsiveness to gonadotrophin in PCOS (15,17,18,42).…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with previous studies (4,(38)(39)(40)(41), the number of total oocytes, metaphase II oocytes, and >14 mm follicles were statistically different in groups in our study, verifying the positive predictive value of baseline AMH levels on the ovarian response to stimulation regimen. The total consumption of gonadotrophins progressively decreased from low to high baseline in the AMH group, which is consistent with previous data indicating that baseline AMH levels positively predict ovarian responsiveness to gonadotrophin in PCOS (15,17,18,42).…”
Section: Discussionsupporting
confidence: 93%
“…Within the ovary, TGF-b superfamily members are expressed in divergent cell types. AMH, a granulosa cell-derived growth factor, has been regarded as a reliable biomarker to predict the ovarian reserve and response (26). The studies on TGF-b superfamily member in ovarian physiology reveal the potential value of this functional superfamily in clinical application with an attempt to predict the ovarian response during COH process.…”
Section: Discussionmentioning
confidence: 99%
“…Signs indicating a reduced follicle number may already be expressed by elevated early follicular FSH levels, so we choose FSH as an indicator of the e cacy of POI modeling 33 . And the Changes in the level of AMH as an indicator of the ovarian follicular reserve was also investigated since AMH can be a predictor for POI patients 34 Since none of the study mentioned the mortality of rats and no incomplete outcome data was found. We detected the 200mg/kg as a safe dose for CTXinduced POI model.…”
Section: Discussionmentioning
confidence: 99%